SP-A binds alpha(1)-antitrypsin in vitro and reduces the association rate constant for neutrophil elastase - Gorrini, Marina (BioMed Central, 2005)
BACKGROUND: α1-antitrypsin and surfactant protein-A (SP-A) are major lung defense proteins. With the hypothesis that SP-A could bind α1-antitrypsin, we designed a series of in vitro experiments aimed at investigating the nature and consequences of such an interaction. METHODS AND RESULTS: At an α1-antitrypsin:SP-A molar ratio of 1:1, the interaction resulted in a calcium-dependent decrease of 84.6% in the association rate constant of α1-antitrypsin for neutrophil elastase. The findings were similar when SP-A was coupled with the Z variant of α1-antitrypsin. The carbohydrate recognition domain of SP-A appeared to be a major determinant of the interaction, by recognizing α1-antitrypsin carbohydrate chains. However, binding of SP-A carbohydrate chains to the α1-antitrypsin amino acid backbone and interaction between carbohydrates of both proteins are also possible. Gel filtration chromatography and turnover per inactivation experiments indicated that one part of SP-A binds several molar parts of α1-antitrypsin. CONCLUSION: We conclude that the binding of SP-A to α1-antitrypsin results in a decrease of the inhibition of neutrophil elastase. This interaction could have potential implications in the physiologic regulation of α1-antitrypsin activity, in the pathogenesis of pulmonary emphysema, and in the defense against infectious agents.